Resilience Against School Bullying: A Study of Verbal and Physical Abuse in Chang Can Dunk (2023) - Zafira Ummu Syahidah; Bambang Irawan (Morphosis: Journal of Literature, 2025)
This study examines the issue of bullying as depicted in Jingyi Shao’s film Chang Can Dunk (2023), with a specific focus on the experiences of the protagonist, Chang, within the context of the high school environment. The study investigates two primary forms of bullying—verbal and physical—highlighted as central challenges faced by the main character. Employing a qualitative descriptive method, this research analyzes selected scenes and dialogue from the film to identify instances of verbal and physical bullying. The theoretical framework is grounded in Dan Olweus’s (1993) bullying typology, which classifies bullying into distinct categories and emphasizes its psychological and social impacts on adolescents. The analysis reveals persistent bullying targeted at Chang based on his appearance, ethnicity, and perceived social standing. The bullying occurs both in overt physical confrontations and more subtle, yet damaging, verbal attacks. These experiences are portrayed as ongoing and influential in shaping the protagonist’s development and self-concept. The film illustrates Chang’s journey toward resilience, demonstrating how internal strength, mentorship, and self-empowerment enable him to confront and ultimately overcome the bullying he faces. This study contributes to the broader discourse on youth representation in media, shedding light on the psychological dynamics of bullying and the importance of supportive environments in fostering adolescent resilience.